Deconstructing Hybrid Work: Technostress, Cognitive Permeability, And The Urgency Of E-Leadership - I Dewa Gede Sayang Adi Yadnya; A. Sobandi A. Sobandi; Agus Rahayu; Lili Adi Wibowo; Yeni Fajrin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The radical transformation toward hybrid work models post-pandemic has redefined organizational boundaries while simultaneously triggering technostress, which threatens employee well-being. This study aims to map the drivers, impacts, and mitigation strategies of technology-induced stress in hybrid work environments through a scoping review approach. Following the PRISMA-ScR protocol, 50 peer-reviewed articles (2020-2025) were synthesized from the Scopus database. Findings indicate that the primary antecedents of technostress are rooted in techno-invasion, the